Cultural Tourism and Sustainable Development: A bibliometric Analysis from 2019 to 2024 - Widodo, Wahyu Indro; Adiyanti, Assyifa Shafia; Suardana, I Ketut; Anggraini, Fera Dhian; Disma, Fatimatuz Zahra; Firdaus, M. Surya (Journal of Information Systems Research and Practice, 2025)
The intersection between cultural tourism and sustainable development is receiving increasing attention, reflecting the growing body of research aimed at balancing cultural heritage preservation with economic growth. However, there are still challenges in integrating tourism with economic aspects and respecting cultural differences. This bibliometric analysis aims to describe the main thematic groups, identify the largest contributing countries, and highlight the leading authors in this field in 2019-2024 using the Vos Viewer software. By leveraging the Scopus database and focused query strings, this research reveals China, Italy and Indonesia as the main contributors, indicating a large publication output and citation impact. The identification of prominent authors underscores their important role in advancing knowledge in this domain. Visual representations of networks across countries and keywords provide insight into collaborative relationships and common themes. The interconnected nature of research activities between countries underscores the importance of international collaboration in promoting sustainable cultural tourism practices. This study underscores the importance of sustainable cultural tourism in driving economic growth and community engagement while preserving cultural heritage. Overcoming challenges and fostering collaboration is critical to ensuring the continued success of cultural tourism as a driver of sustainable development. By contributing valuable insights to the ongoing discourse on cultural tourism and sustainable development, this analysis informs the direction of future research and discussion, thereby facilitating progress in the field.